The Exchange Rate Of Bagan Rambo Fishermen In Barru District. Barru Regency, South Sulawesi - Alpiani Alpiani (Hasanuddin University, 2022)
This study aims to analyze and examine the exchange rate of labour fishers on Bagan Rambo fishing gear in Barru district, Barru Regency. The fishers' exchange rate is used to measure the basic needs of fishers, which considers the income and expenditure of the households of the Bagan Rambo labourers. This type of research uses instrumental case studies. Analyze the poverty of fishers as an instrument for understanding their lives. The results showed that the exchange rate of fishers (NTN) of Bagan Rambo workers was lower than one hundred (88,49%), which means the Bagan Rambo labour fishers cannot meet their basic needs.